COVID-19 Outbreak: Preparing and Protecting the Frontline Battle Force - Habib, Syed Shahid (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
The World Health Organization (WHO) announced in January 2020 that spread of the novel coronavirus disease, COVID-19, is an International Emergency of Public Health. The report mentioned a very high risk of rapid global spread of COVID-19. In March 2020, WHO characterized the outbreak as a pandemic.1 From the start, the medics are at heightened risk of contracting COVID-19 infections. In this global pandemic the health care workers (HCW) have taken the most burden of COVID-19. The doctors, nurses, other medical and ancillary staff have been the frontline warriors in combating this disease. Hundreds of thousands of healthcare workers have been infected and a significant number have paid the ultimate sacrifice.2 There are no true numbers as data has been sketchy but conservative estimates are that more than a thousand doctors and nurses around the world to date have died from COVID-19. The only consolidated worldwide source of data about health workers seems to be Medscape.3 The reports showed that about 500 HCW have succumbed to death in Russia since the spread of COVID-19 started. The National Federation of Physicians and Dentists in Italy shows the names of 168 medical care health professionals who have so far died due to COVID-19, in April 2020 although the list was not yet updated in June.4 The International Council of Nurses reported in June that limited data is available and brought our attention to more than 230,000 COVID-19 infections in health workers worldwide, with more than600 deaths in nurses due to the virus. On 20th of May 2020, the UK Prime Minister Boris Johnson rightly figured out the current counts were about 181 in NHS workers and about 131 in care givers, meaning that the death toll had already crossed 300.5 The UK has the highest health worker deaths in Europe, closely followed by Italy. We do not have any statistics from South East Asia or Middle East. What we hear and see seems to be much less than what it is in actual facts like the tip of an iceberg. It is not just for the sake of data collection. Rather the purpose is to add to the scientific knowledge base which will inform us about the prevention strategies and control measures of COVID-19 infections. Whatever is properly measured will count and despite accolade and applauding, if we do not count and keep accurate data, then actually we have failed to honor and recognize our front line forces, some of whom have already made the ultimate sacrifice. When many countries are compared, the results are much less than expected in some countries. Why did Spain with only slightly fewer COVID-19 deaths only have 29 health workers deaths? How did Spain protect their healthcare workers better?5 Further analysis showed even greater discrepancies and showed that this was not just a blip. “Every one of those who died is a big loss and tragic: the thought of these HCW, is truly heart breaking and they are the beloved ones of family members including parents , siblings, brothers and sisters , losing their lives because of the care taking job they are doing for the humanity. In many cases this should never have happened, and it must never happen again because these losses are multiplied more so because of the additive risks faced by HCW as a result of lack of access to appropriate personal protective equipment (PPE) for their safety. It is the responsibility of key Government organizations to keep all their HCW safe. They should coordinate with the manufactures and make sure proper distribution of PPEs, since they have failed in many instances to arrange for the necessary required resource facilities or levels of innovative equipment and methods which are urgently required to deal with an issue which may take many months to resolve.6 A big question remains that “how many world leaders have tried to put aside any differences to ensure that the provision PPEs is their prime most priority?” We all are aware that it highly challenging to supply the best PPE in right time to the right place, but when there is a will there is a way. It is definitely true that they have the authority and power that can bring a significant change in this emergency situation by negotiations of contracts and help with the manufacturers and distributors of this important and crucial lifesaving equipment.” If we could succeed in doing this we can save more lives for both health care providers and the community in the coming future. How do we look at the situation of those who are fighting on the front lines in this COVID-19 pandemic? Do we realize that they are feeling under pressure? Do we see any organized plans to manage the mental and psychosocial aspects of health for them during this crisis which are in real sense as important as managing of their physical health? The current pandemic is an unprecedented unique challenge and experience for all workers, especially if they have never faced similar situations. Even though, using similar strategies with past experiences to manage times of stress can benefit you now.7 It is you who most likely knows how you can abort or decrease the stress, so do not be hesitant in keeping yourself psychologically and physically well. The team leaders in health care facilities should make sure the protection of all staff members from a continuous ongoing great physical stress and mental strain in this challenging scenario.6,7 They should focus on a longer term occupational work capacity rather than repeated short term crisis responses. They should make policies and must ensure good quality communications to be provided to all staff.8 This might need the following measures;